Adaptation and Validation of a Mobile Phone Dependency Scale in University Students - Suazo, Nia Farach; Avilés Castro, David Ricardo; Vargas Cordero, Isaac Daniel; Joya Herrera, Carolina; Canales Ortiz, Zabdiel Enoc; Reyes Flores, Luis Gerardo; Mejia Rivera, Kevin Arnaldo (LACCEI, 2025)
Currently, among the main dependencies identified by the WHO, a new technological one has emerged related to mobile phone use—a phenomenon that has been the subject of study in multiple contexts. In this regard, the adaptation and validation of the Mobile Phone Dependency Test is proposed. Methodologically, a quantitative, cross-sectional, explanatory study was conducted with a sample of 229 university students aged 18 to 24, who voluntarily and freely participated under informed consent. The study obtained a statistical reliability of 0.80 using Cronbach’s Alpha and identified a factorial structure composed of three factors—withdrawal, control, and tolerance—as represented in the original scale but in a reduced 15-item version, supported by a Confirmatory Factor Analysis (CFA) for this adaptation. At the results level, the model fit measures were favorable for the short Spanish-language version. Factorially, tolerance associated with usage showed higher scores compared to the other two factors, confirmed by a statistical mean of 3.76/5. However, it is suggested to broaden the sample spectrum, as the scores are sensitive to sample size—a limitation not considered critical for this study but rather an opportunity for future research.